Efektivitas Kurikulum Merdeka dalam Mengembangkan Kompetensi Profesional Guru di SMP Negeri 8 Tebing Tinggi - Mulya, Sri; Akrim, Akrim; Isman, Muhammad (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2025)
Knowing and analyzing the effectiveness of the Independent Curriculum in developing teacher professional competence at SMP Negeri 8 Tebing Tinggi. This research was carried out at SMP Negeri 8 Tebing Tinggi. The type of research was qualitative using observation, interview and documentation data collection techniques. The research subjects were the principal, deputy principal and teachers. research results Professional competency planning at SMP Negeri 8 Tebing Tinggi processes teaching materials in a pleasant atmosphere and utilizes technology as a learning resource. Implementing an independent curriculum in improving professional competence teachers are able to develop sustainably.Evaluation of the independent curriculum on effectiveness in developing the professional competence of teachers at SMP Negeri 8 Tebing Tinggi includes teachers mastering material, structure, concepts and thought patterns. Both teachers are able to utilize information and communication technology to develop themselves in communicating. Students are asked to practice or demonstrate what they have learned during the assessment. In contrast, project assessment is a way of assessing assignments given by teachers to students individually or in groups within a certain period of time. School intervention to ensure teachers and students are creative and detailed. The effectiveness of the level of tendency to increase the professional competence of teachers with a mean value of 78.11% and a median of 79.00% so that the principal's leadership has an impact on the professional competence of teachers at SMP Negeri 8 Tebing Tinggi.